Distal and lateral toenail onychomycosis caused by Trichophyton rubrum: treatment with photodynamic therapy based on methylene blue dye - Linton Wallis Figueiredo Souza; Simone Vilas Trancoso Souza; Ana Cristina de Carvalho Botelho (Sociedade Brasileira de Dermatologia, 2014)
The study showed the effectiveness of photodynamic therapy based on methylene blue to treat severe distal and lateral subungual toenail onychomycosis. 22 patients were divided into two groups: group A consisting of 11 patients with severe toenail onychomycosis and group B consisting of 11 patients with mild-to-moderate toenail onychomycosis. All patients had onychomycosis caused by Trichophyton rubrum. The patients were treated with sessions of 2% methylene blue aqueous solution irradiated with light emission diode device with 630 nm and 36 J/cm2 biweekly for six months. The clinical response was significantly better in patients with mild-to-moderate (100%) onychomycosis compared with patients with severe onychomycosis (63.6%).